2020
DOI: 10.14814/phy2.14551
|View full text |Cite
|
Sign up to set email alerts
|

Indices of leg resistance artery function are independently related to cycling V̇O 2 max

Abstract: Purpose While maximum blood flow influences one's maximum rate of oxygen consumption (V̇O2max), with so many indices of vascular function, it is still unclear if vascular function is related to V̇O2max in healthy, young adults. The purpose of this study was to determine if several common vascular tests of conduit artery and resistance artery function provide similar information about vascular function and the relationship between vascular function and V̇O2max. Methods Twenty‐two healthy adults completed multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…On the other hand, the lack of a significant association between V˙O 2max and the %FMD can be justified by the fact that the same percent change in diameter would have a far less pronounced effect on blood flow in a smaller compared with a larger artery. Gifford and colleagues (39) recently reported similar findings, showing no relationship between V˙O 2max and %FMD but significant correlations between V˙O 2max and indices of resistance artery function. These findings and our findings are in contrast with those from a meta-analysis by Montero (40), who suggested that %FMD is related to V˙O 2max .…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, the lack of a significant association between V˙O 2max and the %FMD can be justified by the fact that the same percent change in diameter would have a far less pronounced effect on blood flow in a smaller compared with a larger artery. Gifford and colleagues (39) recently reported similar findings, showing no relationship between V˙O 2max and %FMD but significant correlations between V˙O 2max and indices of resistance artery function. These findings and our findings are in contrast with those from a meta-analysis by Montero (40), who suggested that %FMD is related to V˙O 2max .…”
Section: Discussionmentioning
confidence: 69%
“…Overall, inflammation, oxidative stress, and autonomic dysfunction can, independently or concurrently, modulate vasomotor tone and contribute to peripheral vascular dysfunction post-COVID-19. Given the link between lower limb vasodilatory capacity and V̇ o 2peak ( 59 , 60 ), this vascular dysfunction is also likely to compromise O 2 delivery to the exercising muscle, leading to reduced exercise tolerance and physical function following COVID-19 infection. It will be important to determine whether this vascular dysfunction is transient or if it increases future risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated greater reactive hyperemia among physically active individuals than sedentary individuals [24,25]. With a sample size of 10 subjects from a variety of training backgrounds, it is unknown how well these results apply to the broader population or specific patient populations.…”
Section: Experimental Considerationsmentioning
confidence: 98%
“…The leg was rested at 90 • of knee flexion to minimize the impact that differing degrees of knee flexion have on the blood flow response to knee extension exercise [23]. Since the hyperemic response to knee extension is influenced by the amount of external work performed during a contraction [24,25], the displacement distance of the weight was limited to 15 cm for each contraction. Limiting the displacement distance to 15 cm also prevented the subjects from fully extending and "locking out" their knees, which could introduce undesired bouts of rest between concentric and eccentric contractions.…”
Section: Familiarization Visitmentioning
confidence: 99%
See 1 more Smart Citation